HISTORIOGRAPHY AND SOURCES OF THE ESTONIAN BOOK SCIENCE IN THE YEARS 1918–1944 - MÖLDRE, AILE; REIMO, TIIU (Knygotyra, 2015)
The article characterises the formation and development of the Estonian book science during the years 1918–1944 and gives an overview about the research on the period in the second half of the 20th century. Book science as an independent field of research started to develop in Estonia in the 1920s. Friedrich Puksoo and Richard Antik became the most significant researchers. F. Puksoo is the author of the first general overview of the history of the Estonian book, published in 1933. R. Antik made a major contribution to retrospective bibliography and book statistics. 138 publications treating the field of book science were published in Estonian language in 1918–1944. The analysis of these publications demonstrates a considerable rise in the number of publications on book history during the Year of the Book which was celebrated in 1935–1936. By the 1930s book studies had become an independent field of research which tackled both historical and contemporary issues. The article also includes a thematic analysis of the publications, which are divided into eight groups: general treatments, research on printing, publishing, book dissemination, book art, studies of a concrete book, statistical analysis and works on bibliophilism. As to the thematic structure of the publications, general treatments were the most numerous (34), history of printing, book dissemination, studies on a concrete book and book art were also popular topics of research whereas the smallest number of publications (8) were devoted to bibliophilism. The researchers of that time have made a valuable contribution in the development of book research by gathering rich factual data, elaborating the basic principles of book statistics, compiling the first general treatments of book history. During the first post-war decade, the Stalinist era, research on the book history of the the period of independence in 1918–1940 was discontinued. The treatment of the topics connected with publishing and distribution of books in 1918–1940 enlivened only during the 1970s. The leading researcher Mare Lott has written articles published in Estonian and in foreign languages. The results of her reasearch are presented most completely in her unpublished dissertation. For the larger public they are available in the collective monograph “The Estonian Book 1525–1975”, issued in 1978. Numerous diploma works and Bachelor’s thesis have been written on this period under her guidance, but the results of these works have not been published. Since perestroika the ideological constraints in the treatment of the period disappeared, but the research of the book branch of this era has not been very intensive. Among the most outstanding achievements are the collections of articles dedicated to the two leading book reserachers Fr. Puksoo and R. Antik. A research group has been formed in the Tallinn University to prepare a comprehensive work on the book branch of that period which would tackle the topic from the contemporary viewpoint.